Evaluation of plant products against aphid (Myzus persicae Sultz) transmission of mosaic disease of leaf mustard (Brassica juncea var. rugosa) - and I.M. SINGH, PH. SOBITA DEVI*, L. RANJANA DEVI (Indian Phytopathology, 2008)
Leaf and seed kernel extracts of neem (Azadiracta indica) and Jatropha curcas along with a botanical, Neemarin were tested against the aphid transmission of mosaic disease of leaf mustard (Brassica juncea var. rugosa). All the plant products could influence the transmission. In field, among different plant products, the botanical Neemarin (0.2%) was found best in reducing the disease to 56.94 per cent reduction over control followed by neem seed kernel extract (0.5%) with 53.46 per cent and neem leaf extract (0.5%) with 46.53 per cent reduction over control. However, the check treatment dichlorovos (0.04%) showed highest effectiveness in inhibiting virus transmission wherein the per cent infection was hardly 17.36 per cent and the reduction over control was 61.11 per cent. Jatropha leaf extract was less effective but was better than the control (water). In the laboratory trial too, dichlorovos (0.04%) treated plants showed lowest infection (11.66 per cent) followed by Neemarin (0.2%) (13.33 per cent) and neem seed kernel extract (0.5%) with 16.66 per cent infection. Incubation period of the virus was found to be longer in all the treated plants than in the untreated control.